Determinan Prevalensi Balita Stunting 34 Provinsi di Indonesia Tahun 2017-2022 - Deswira Aulia; Toto Gunarto; Asih Murwiati; Emi Maimunah (Jurnal Simki Economic, 2024)
Stunting is a condition where toddlers fail to grow due chronic malnutrition. Indonesia is the second largest country with the highest prevalence rate in Southeast Asia.Meanwhile, the Indonesian government has implemented various efforts to reduce the prevalence of stunting. This study aims to determine the influence of the average length of mother's schooling, exclusive breastfeeding, level of completeness of toddler immunization, posyandu activities, inadequate food consumption and good sanitation on the prevalence of stunting. Using OLS panel data regression, the results showed that the average number of years of schooling for women, posyandu activity, and adequate sanitation had a significant negative influence on the prevalence of stunting in 34 provinces in Indonesia. And inadequate food consumption has a significant positive effect on the prevalence of stunting in Indonesia in 2017-2022. Meanwhile, exclusive breastfeeding and the level of complete immunization for toddlers do not have an effect on the prevalence of stunting in Indonesia in 2017-2022.